The Effect of Brown Algae (Sargassum sp) Extract on Wound Healing: pH gel ; diameter - Tri Wahyuni Bintarti; Meidyta Sinantryana Widyaswari (Jurnal Ilmu Kesehatan dan Kesehatan, 2022)
Backgroud: The wound care method that is currently developing uses the principle of moisture balance which is also known as the modern dressing method.  Seaweed is a potential commodity in Indonesia, which has been widely used as a medicinal ingredient. However, the use of seaweed in the form of hydrogel ointment in the treatment of burns has not been widely studied. Therefore, this study was conducted to determine the effect of giving seaweed extract  (Sargassum sp.) in the form of hydrogel ointment to burns. Methods: The design in this study was an experimental study with a randomized post-test only control group design, using musmusculus mice. This study was divided into 4 groups, group 1 was a negative control without treatment, group 2 was a group with burns and was given bioplacenton, group 3 was a burn group treated with 5% Sargassum sp extract hydrogel ointment and group 4 was a burn group given 5% ointment. Sargassum sp extract hydrogel ointment 10%. The treatment was carried out for 14 days and evaluated the diameter of the burn and the percentage of burn healing. Results: The results of this study showed that the difference in burn diameter at 0 days and after 14 days in the negative control group experienced a difference of 1.2 cm with a healing percentage of 44.85%. In treatment group 1, there was a difference in diameter of 1.2 cm, with a healing percentage of 49.41%, the 2-day treatment group obtained a difference in diameter of 1.2 cm, with a healing percentage of 50.31%, and in the positive control group a wound diameter of 1.0 cm, while the percentage of cure is 55.75%. The results of statistical tests on the percentage of wound healing between groups were not significantly different. Conclusion: In this study the seaweed extract  (Sargassum sp.) formed in the hydrogel ointment did  ot affect the healing of burns, this may be due to the long duration of administration.